2021
DOI: 10.1101/2021.01.25.21250437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking the mental health of home-carers during the first COVID-19 national lockdown: evidence from a nationally representative UK survey

Abstract: BackgroundUnpaid carers who look after another member of their household (home-carers) have poorer mental health than the general population. The first COVID-19 national lockdown led to an increasing reliance on home-carers and we investigate the short and longer-term impact of lockdown on their mental health.MethodsData from 9,737 adult participants (aged 16+) from the UK Household Longitudinal Study (Understanding Society) were used to explore changes in 12-item General Health Questionnaire (GHQ-12) score be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
3
1
Order By: Relevance
“…While Klaus and Ehrlich [31] only provide descriptive results, their findings are confirmed by our results. Yet, Whitley et al [33] found gender differences only at the very beginning of the pandemic and Todorovic et al [32] found no significant differences, while our results indicate a significant gender difference in the second wave during the pandemic. Regarding the findings from Todorovic et al [32], these differences in results may be due to their study not accounting for confounders and analyzing a small convenience sample.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…While Klaus and Ehrlich [31] only provide descriptive results, their findings are confirmed by our results. Yet, Whitley et al [33] found gender differences only at the very beginning of the pandemic and Todorovic et al [32] found no significant differences, while our results indicate a significant gender difference in the second wave during the pandemic. Regarding the findings from Todorovic et al [32], these differences in results may be due to their study not accounting for confounders and analyzing a small convenience sample.…”
Section: Discussioncontrasting
confidence: 84%
“…Previous research from during the pandemic, which came primarily from international studies, was less consistent. Our findings add to results from studies from China [28], Italy [29], the USA [5], the UK [33], and Serbia [32], which also found poorer mental health among female caregivers. While Klaus and Ehrlich [31] only provide descriptive results, their findings are confirmed by our results.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…People living alone are particularly at risk [41, 20, 6, 45, 44], which makes sense given the association between loneliness and depressive symptoms during the pandemic [19]. People in poor partner relationships [67 (Dickerson et al, 2020) and with young children [17, 6] have also experienced worse mental health, particularly early on in the March 2020 lockdown for those caring for young children [68]. Those caring for adult children experienced a sustained increase in anxiety until July 2020 [68].…”
Section: Resultsmentioning
confidence: 99%
“…People in poor partner relationships [67 (Dickerson et al, 2020) and with young children [17, 6] have also experienced worse mental health, particularly early on in the March 2020 lockdown for those caring for young children [68]. Those caring for adult children experienced a sustained increase in anxiety until July 2020 [68]. Living with children has also been linked to increased alcohol consumption [69].…”
Section: Resultsmentioning
confidence: 99%